Creole maize from South-West of São Paulo, Brazil: diversity and seed quality - Lima, Laís Stefany de Carvalho Falca; Fachini, Cristina; Silva, Victor Roberto da; Borges, Janice Rodrigues Placeres; Forti, Victor Augusto (Revista Mexicana de Ciencias Agrícolas, 2022)
The maintenance of creole seeds promotes preservation of agrobiodiversity and family autonomy. For this reason, seeds quality is essential in the context of creole seeds because directly impacts the improvement of the production field and, consequently, its continuous existence. The study evaluated the diversity and the seed quality of creole maize seeds in two harvests in the South-West of São Paulo, Brazil, an important maize production site in Brazil. Seeds from both harvests (2019 and 2020) were evaluated regarding the physical (physical aspects, one test seed mass, test of infestation), physiological (water content, germination test, seedling emergence in soil, emergence speed index and cold test) and health potential (blotter test). Among 20 lots collected, the seeds were classified into five varieties according to family famers perception. It was observed a variation in terms of physical, physiological and health quality between the seed lots. The lots harvested in 2020 had the highest values of size, 1000 seed mass, germination and vigor. The blotter test identified for both harvests, mainly in 2019, high incidence of Aspergillus sp. and Penicillium sp., considered as storage fungi. Therefore, the variation in seed quality between the harvest refers mainly to the characteristics of the storage process performed. More studies on better strategies for creole maize seed storage are necessary to guarantee seed quality, since low seed quality is a risk for losing these materials.